2018
DOI: 10.2217/fvl-2018-0110
|View full text |Cite
|
Sign up to set email alerts
|

The Early Bird Gets the Worm: Benefits and Future Directions With Early Antiretroviral Therapy Initiation in Primary Hiv Infection

Abstract: Primary HIV infection is defined as the first few weeks after infection where plasma viremia is rapidly increasing. Early diagnosis of primary HIV infection enhances the tendency of behavioral changes in newly infected individuals to prevent secondary HIV transmission. Early antiretroviral therapy (ART) benefits individuals by reducing plasma viral load, gut damage, microbial translocation and subsequent systemic immune activation. Early ART leads to the establishment of low HIV reservoir size that may contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…These results suggest that plasma levels of CXCL13 progressively increases with HIV disease progression and is decreased without normalization upon initiation of ART. This is in line with previous findings that ART results in a decrease without normalization of systemic immune activation (40). Multivariate analysis confirmed that elevated CXCL13 levels among PLWH were independent of the effect of age, sex, HIV viral load, CD4 T cell count, and inflammatory markers.…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that plasma levels of CXCL13 progressively increases with HIV disease progression and is decreased without normalization upon initiation of ART. This is in line with previous findings that ART results in a decrease without normalization of systemic immune activation (40). Multivariate analysis confirmed that elevated CXCL13 levels among PLWH were independent of the effect of age, sex, HIV viral load, CD4 T cell count, and inflammatory markers.…”
Section: Resultssupporting
confidence: 93%
“…Due to the success of ART, the life expectancy and quality of life of PLWH has dramatically improved over the course of the last decade. While early initiation of ART is associated with lower reservoir size and reduced immune activation, PLWH on ART still suffer from unrecovered epithelial gut damage and chronic immune activation ( 89 ). It has been recently reported that epithelial gut damage precedes systemic immune activation in a SIV-infected rhesus macaque model ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poorer youth retention has been observed throughout the region: a large cohort analysis of ART patients in sub-Saharan Africa found youth (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) to have a higher risk of attrition than older adults [5]. ART care improves outcomes of people living with HIV and reduces transmission [6][7][8][9]. As youth on ART are a growing population [10], it is important to identify effective strategies to address youth-specific needs and prevent attrition from care.…”
Section: Introductionmentioning
confidence: 99%